Respuesta :
x = 3
2(4x - 3) - 8 = 4 + 2x
1. Distribute
8x - 6 - 8 = 4 + 2x
2. Collect like terms
8x - 14 = 4 + 2x
3. Collect like terms again (add 14 and subtract 2x)
6x = 18
4. Divide by 6
x = 3
2(4x - 3) - 8 = 4 + 2x
1. Distribute
8x - 6 - 8 = 4 + 2x
2. Collect like terms
8x - 14 = 4 + 2x
3. Collect like terms again (add 14 and subtract 2x)
6x = 18
4. Divide by 6
x = 3
Expand the bracket to get 8x - 6 - 8= 2x + 4
Take away 2x from both sides:
6x - 6 = 4
Add 6 and 8 to both sides and you end up with
6x = 18
Now for this step you divide both sides by 6 so that the coefficient of x is 1. You end up with x = 3. Hope that this helps and have a great rest of your day.
Take away 2x from both sides:
6x - 6 = 4
Add 6 and 8 to both sides and you end up with
6x = 18
Now for this step you divide both sides by 6 so that the coefficient of x is 1. You end up with x = 3. Hope that this helps and have a great rest of your day.